Internalization of Muticultural Education Values in Improving the Quality of Graduates at Pesantren Assalam Sungai Lilin - Sayid Habiburrahman; Suroso; Fitri Mulyati (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The results of this study show that; first, the values of muticultural education that are instilled are: democracy, mutual respect, tolerance, mutual respect, justice and equality, brotherhood, togetherness, and cooperation. Second, the process of internalizing muticultural education values is applied in the form of; curriculum planning, democracy in discussions and workshops, interaction between teachers and students, and democratic evaluation. Third, improving the quality of alumni through; acceptance of students, distribution of alumni benefits in the community and other surrounding places formally and non-formally. Fourth, supporting factors are; visionary kiyai and sustainable integrated Islamic education system, textbook curriculum, while inhibiting factors; limited muticultural understanding, need to increase cultural and interfaith dialogue, limited understanding of the meaning of tolerance. The values of muticultural education can be influenced by integration in a sustainable integrated Islamic education system through the curriculum content of textbooks and pesantren books, coaching pattern time, and a conducive climate environment.